Dissolution Study on Grape Polyphenol Hard Gelatin Capsule Dietary Supplements - Lyu, Weiting; Omar, Thamer; Patel, Harna; Rodriguez, David; Ferruzzi, Mario G.; Pasinetti, Giulio M.; Murrough, James W.; Muzzio, Fernando J.; Simon, James E.; Wu, Qingli (Frontiers in Nutrition, 2021)
Methods for a dissolution study by ultra-high performance liquid chromatography/triple quadrupole mass spectrometry (UHPLC-QqQ/MS) analysis of grape polyphenol dietary supplements, namely, grape seed extract (GSE) and resveratrol (RSV) capsules, were developed following the guidance of United States Pharmacopeia (USP) <2040>. Two dissolution media, 0.1 N hydrochloric acid (pH 1.2) and 0.05 M acetate buffer (pH 4.6), were evaluated with dissolution apparatus (USP 1), 100 rpm rotation speed, and 900 ml dissolution medium volume. Dissolution profiling was performed over 120 min. Major phenolic compounds of gallic acid, catechin, epicatechin, and procyanidin B2 were quantitated to obtain the dissolution profile of GSE capsules, and trans-RSV was used for RSV capsules. Results indicated that the released trans-RSV for RSV capsules in both of the dissolution media meets the USP standards, and that for the GSE capsules, all the four marker compounds passed the dissolution test in the HCl medium but did not reach a 75% release within 60 min in the acetate buffer. These promising results suggest that the general USP dissolution protocols are adequate for the successful release of RSV capsules in HCl medium and acetate buffer and GSE capsules (in HCl medium), but may be inadequate for GSE capsules in acetate buffer. These results showed that under a low pH of 1.2 (simulated stomach environment), bioactive compounds were released on time from the GSE capsules and met the USP guidelines; however, under a higher pH of 4.6 (simulated duodenum environment), the same biomarkers failed, suggesting the need to further improve the dissolution of GSE over a wider range of pH environments to enhance bioavailability and efficacy.